Rediscovery and redescription of Blakea villosa (Melastomataceae), an endemic species from southern Peru, with preliminary observations on the flower visitors - Fernandez-Hilario, Robin; Sato, Akira A. Wong; Revilla, Italo; Churata-Salcedo, Julissa (Phytotaxa, 2025)
Blakea villosa was published by Alfred Cogniaux in 1908 from material collected in 1905 by Augusto Weberbauer in the Urubamba River valley (Department of Cusco) in southern Peru. Based on recent expeditions to Cusco and examination of herbarium specimens, in this article, we provide a morphological redescription together with taxonomic comments, an identification key for related species (Blakea eden, B. hispida and B. repens), and ecological notes on the floral visitors of Blakea villosa. This species is distinguished by its nodes with fimbriate interpetiolar flaps, abaxial leaf blades with dense velutinous indumentum, petals 30.5–32 mm long, style incurved at apex, and fruits with calyx lobes inflexed, and its flowers are visited by bumblebees and stingless bees, among which we believe the former to be the main pollinators.